Produksi Karotenoid oleh Rhodosporidium paludigenum dalam Media Yeast Peptone Dextrose dengan Suplementasi Molase - Renna Eliana Warjoto; Theresia Andriana; Bibiana Widiati Lay (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Carotenoid pigments are commonly found in fruits and vegetables, but carotenoids can also be produced by microorganisms such as yeasts. Carotenoids have several benefits, including antioxidant compounds and vitamin A precursors. Production of carotenoids by microorganisms depends on various factors, such as pH, temperature, and nutrient content in the media. This study aimed to determine the optimum concentration of molasses supplementation and the initial pH of the media for carotenoid production by the red yeast Rhodosporidium paludigenum. In this study, the red yeast was cultivated in Yeast Peptone Dextrose (YPD) media supplemented with molasses, with a total sugar concentration of 2% in the media. This study had a factorial design with eight treatment groups, i.e., molasses supplementation of 0%, 25%, 50%, and 75% in the media with initial pH of 5 and 6 for each molasses supplementation. The results showed that the culture in the media with supplementation of 25% molasses and pH 5 produced the highest levels of carotenoids when compared to those with 50% and 75% molasses supplementation concentrations. The yields of β-carotene and xanthophyll over biomass dry-weight in the media with 25% molasses supplementation at pH 5 were 26.67 μg/g and 31.15 μg/g, respectively. Nevertheless, the red yeast in the media without supplementation (0%) produced the highest carotenoid concentration among all treatments.